Biodiesel production from palm oil using hydrated lime-derived CaO as a low-cost basic heterogeneous catalyst. (15th January 2016) - Roschat, Wuttichai; Siritanon, Theeranun; Yoosuk, Boonyawan; Promarak, Vinich
Graphical abstract: Hydrated lime-derived CaO can be utilized as high efficient heterogeneous solid catalyst for transesterification of palm oil to biodiesel product. Highlights: CaO with high surface area and pore volume was successfully prepared from hydrated lime using a simple method. Hydrated lime-derived CaO were used as a catalyst in transesterification of palm oil to biodiesel. Over 97% FAME yield was achieved from transesterification of palm oil in 2 h. This CaO has high potential for applications as green and low-cost catalyst. Abstract: In this study, hydrated lime-derived calcium oxide (CaO) was used as a catalyst for the transesterification of palm oil. The catalysts were characterized by TG-DTA, XRD, XRF, FT-IR, SEM, Hammett indicator method, TPD-CO2 and BET by N2 adsorption. Under the optimal conditions at catalyst loading of 6 wt.%, methanol/oil molar ratio of 15:1, reaction temperature 65 °C, and stirring rate of 200 rpm; 97% yield of biodiesel could be achieved in 2 h. Effects of water amount were investigated and the catalyst could tolerate high water content of 5 wt.%. The kinetic of the reaction followed pseudo-first order with the activation energy ( Ea ) of 121.12 kJ/mol and frequency factor ( A ) of 1.203 × 10 17  min −1 . After treatments, high quality biodiesel was obtained which indicated that the very cheap hydrated lime-derived CaO showed excellent catalytic activity and high potential for applications in biodiesel production.